1986
DOI: 10.1182/blood.v67.1.105.105
|View full text |Cite
|
Sign up to set email alerts
|

Progressive dysfunction of monocytes associated with iron overload and age in patients with thalassemia major

Abstract: We evaluated phagocytic and lytic activities of peripheral blood monocytes (PBMo) from patients with thalassemia major (ThP) using C pseudotropicalis as the target. PBMo from ThP showed decreased lytic activity (P less than .001), whereas the phagocytic activity did not differ from that of the controls. Significant inverse correlations were found between lytic activity of PBMo and age of patients (r2 = .47; P less than .01) and also between lytic activity and serum ferritin levels (r2 = .65; P less than .001).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The reduced killing activity of PMN was observed at 60 min of incubation. A number of investigators have shown that ingestion of C. albicans by PMNs of thalassemia patients was normal (17–19). However, these data were different from others who utilized Escherichia coli , baker's yeast (16, 20, 21), Salmonella typhi , and Staphylococcus aureus (22).…”
Section: Discussionmentioning
confidence: 99%
“…The reduced killing activity of PMN was observed at 60 min of incubation. A number of investigators have shown that ingestion of C. albicans by PMNs of thalassemia patients was normal (17–19). However, these data were different from others who utilized Escherichia coli , baker's yeast (16, 20, 21), Salmonella typhi , and Staphylococcus aureus (22).…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38][39][40][41][42] Immune dysfunction and increased susceptibility to infection also has been demonstrated in patients and animals with secondary forms of iron overload. 29,[43][44][45][46][47][48][49] Enhanced iron-dependent microbial growth in combination with defects in cell-mediated immunity and impaired phagocytosis may have contributed to the mortality from infection in our patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil function is impaired (32)(33)(34). Peripheral blood monocytes show impaired lytic activity (35) and natural killer cells show impaired activity against target cells (36).…”
Section: Iron Statusmentioning
confidence: 99%